On the nonstationary deforming of an elastic layer under mixed boundary conditions - Kubenko, V.D. (Reports of the National Academy of Sciences of Ukraine, 2015)
The problem to determine the stressed state of an elastic layer under nonstationary normal loading is considered. A mixed boundary problem is formulated, and its solution is built by using the Laplace and Fourier integral transforms. The exact inverse of transforms is evaluated. As a result, the analytical solution is obtained, and it determines a stress and a displacement at an arbitrary point of the layer. The analysis of the essential features of wave processes is performed.